2021
DOI: 10.3389/fvets.2021.630686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arginine Supplementation on Serum Metabolites and the Rumen Bacterial Community of Sika Deer (Cervus nippon)

Abstract: Velvet antler is a regeneration organ of sika deer (Cervus nippon) and an important Chinese medicine, and nutrient metabolism affects its growth. Here, we investigated the effects of arginine supplementation on antler growth, serum biochemical indices, and the rumen bacterial community of sika deer during the antler growth period. Fifteen male sika deer (6 years old) were randomly assigned to three dietary groups, which were supplemented with 0 (n = 5, CON), 2.5 (n = 5, LArg), or 5.0 g/d (n = 5, HArg) L-argini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
4
11
0
Order By: Relevance
“…The dominant genera of Bac taxa (Fig. 4 and Supplementary Table S5 ) revealed by amplicon-seq in the present study were consistent with the ruminal microbiome reported previously in sika deer 16 , 17 , 19 and related species (wild roe deer 13 , elk 14 , 18 , reindeer 20 , ruminants 6 ). Of the previous reports, Henderson et al 6 reported the dominant core rumen bacteria of 32 species of ruminants and a total of 742 individual animals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The dominant genera of Bac taxa (Fig. 4 and Supplementary Table S5 ) revealed by amplicon-seq in the present study were consistent with the ruminal microbiome reported previously in sika deer 16 , 17 , 19 and related species (wild roe deer 13 , elk 14 , 18 , reindeer 20 , ruminants 6 ). Of the previous reports, Henderson et al 6 reported the dominant core rumen bacteria of 32 species of ruminants and a total of 742 individual animals.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, high-throughput 16S and 18S small subunit ribosomal RNA (rRNA) gene sequencing (amplicon-seq) has become available for the analysis of rumen microbial community diversity 12 19 . Studies have reported species differences among red deer, roe deer, and moose 12 and in association with diet in livestock and wild deer 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The dominant genus of Bac taxa (Fig. 3A and Table S1) revealed by amplicon-seq in the present study were consistent with the ruminal composition reported previously in sika deer [16,17,19] and related species (wild roe deer [13], elk [14,18], reindeer [20], ruminants [6]). Of the previous reports, Henderson G et al [6] reported the dominant core rumen bacteria in ruminants from 32 species and a total of 742 individual animals.…”
Section: Discussionsupporting
confidence: 91%
“…The pathway and function grouped by gene symbol and the sum of DE taxa that correlated with at least 1 annotated DE transcript in the gene symbol were as follows: the cellular component of agellin (gene symbol: FLA, FLA2, FLAB1, and FLAB2) (number of DE taxa = 31), the Embden-Meyerhof-Parnas (EMP) glycolysis pathway (G3P, GLGC, PGK, and ENO) (N = 21), pyruvate fermentation to lactate (LDH) (N = 9), bacterial toxin (FRPC) (N = 9), phosphoenolpyruvate: carbohydrate phosphotransferase (PTS) (PT1, PTHP, and PTSBC) (N = 8), the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway (ISPH) (N = 8), and sucrose catabolism (SCR) (N=7). The top DE taxa associated with annotated DE transcripts were as follows: uncultured species of g_Prevotella 1 (number of annotated DE transcripts = 28), Eubacterium ruminantium (N = 27), unidenti ed rumen bacterium RFN92 of g_Prevotella 1 (N = 26), uncultured rumen bacterium of g_Lachnoclostridium 10 (N = 20), and bacterium XPB4001 of g_Prevotella 1 (19).…”
Section: Taxonomic Analysis Of Ruminal Communities Using Amplicon-seqmentioning
confidence: 99%
See 1 more Smart Citation